Performance evaluation of joint path and spectrum diversity based routing protocol in Cognitive Radio Ad Hoc Networks under critical conditions - Che-Aron, Zamree; Hassan Abdalla Hashim, Aisha; Abdullah, Khaizuran; Hassan, Wan Haslina; Rahman, Md. Arafatur (Maxwell Scientific Organization, 2012, 2015)
Cognitive Radio (CR) technology has been introduced to solve the problems of spectrum underutilization and spectrum scarcity caused by improper spectrum management policies. The main concept of Cognitive Radio Ad Hoc Network (CRAHN) is that, in a wireless ad hoc network, the unlicensed users (or Secondary Users (SUs)) are allowed to access the temporally unused licensed spectrum bands for data communications without harmful interference to the licensed users (or Primary Users (PUs)). In CRAHNs, the mobile SUs communicate with each other without the use of any centralized network infrastructure. Routing in CRAHNs is an important task and faces various challenges including PU interference, frequent network topology changes, energy constraint, volatile bandwidth and fragile connectivity. In this study, an attempt is made to evaluate the performance of the Dual Diversity Cognitive Ad-hoc Routing Protocol (D2CARP) in CRAHNs under critical conditions, i.e., high node mobility rate and number of PUs. The D2CARP protocol is a joint path and spectrum diversity based routing protocol for CRAHNs. The performance evaluation is conducted through simulation using NS-2 simulator. The performance metrics to be considered include average throughput, percentage of packet loss, average end-to-end delay and average jitter. The simulation results prove that the protocol performance is significantly affected in the networks with high number of PUs and mobility rate, leading to high path failure rate and severe service outages.